2003
DOI: 10.1097/00041552-200303000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-associated hypertension and kidney disease

Abstract: Despite considerable progress in understanding the pathophysiology of obesity, there are still no specific guidelines for the treatment of obesity hypertension other than weight reduction. Special considerations for obese hypertensive patients, in addition to controlling blood pressure, are correcting the metabolic abnormalities and protecting the kidneys from injury. This remains an important area for further research, especially in view of the current 'epidemic' of obesity in most industrialized countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
1
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 32 publications
3
104
1
6
Order By: Relevance
“…21 As with obesity-induced hypertension and diabetes, the pathophysiology of obesity-related kidney disease may function through more subtle mechanisms, such as a variety of hormonal and cytokine influences. 31,32 Further study is needed on the mechanisms by which weight gain increases CKD independent of obesity, hypertension, and diabetes.…”
Section: ͻ0001mentioning
confidence: 99%
“…21 As with obesity-induced hypertension and diabetes, the pathophysiology of obesity-related kidney disease may function through more subtle mechanisms, such as a variety of hormonal and cytokine influences. 31,32 Further study is needed on the mechanisms by which weight gain increases CKD independent of obesity, hypertension, and diabetes.…”
Section: ͻ0001mentioning
confidence: 99%
“…Nevertheless, it is of note that one study found a gender-related difference in the association between obesity and CKD (9), whereas other reports did not (4,5). Obesity increases renal sodium reabsorption, which results in an elevation of blood pressure (6,10,11) and may explain the observed link between obesity and CKD, as hypertension is one of the most important factors associated with the progression of both diabetic and nondiabetic CKD (7). On the other hand, Kramer et al noted a significant association between obesity and the risk for CKD, defined as ≥ 1+ proteinuria and/ or eGFR < 60 mL/min/1.73 m 2 , in a cohort of hypertensive adults, which was statistically significant after adjustment for blood pressure and diabetes (8).…”
Section: Introductionmentioning
confidence: 97%
“…Several cross-sectional and longitudinal epidemiological studies have shown that obesity may increase the prevalence and incidence of chronic kidney disease (CKD) (4)(5)(6)(7)(8). Care must be taken in interpreting these data, since several of the studies have diagnosed CKD based on an estimated glomerular filtration rate (eGFR) lower than a certain cutoff value, while others have defined CKD based on either low eGFR or the presence of albuminuria/proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in this population sample of hypertensive patients with ECG signs of left ventricular hypertrophy, estimated creatinine clearance was significantly reduced in thin individuals to a level comparable to the reduction detected in class II-III obesity. 5 Because in the LIFE study, thin body build was as predictive of cardiovascular death as morbid obesity, renal dysfunction might play a role as an accelerator of impairment of arterial system. 47 Although the 2 extremes of the body build distribution appear to be prognostically similar, participants with normal weight, overweight, and even class I obesity (ie, BMI 20 to 35 kg/m 2 ) did not differ substantially in cardiovascular event rate.…”
Section: Thin Individuals and Hypertensionmentioning
confidence: 99%
“…[1][2][3][4] Obesity predisposes to hypertension because of concomitant metabolic and hemodynamic abnormalities, yielding both increased circulating volume and inadequate lowering of systemic resistance. 1,5,6 Hypertension in obesity, therefore, is characterized by combined volume and pressure overload, even more than in normal-weight subjects with hypertension, and the cardiocirculatory burden is thought, generally but not invariably, 7 to be more severe. There is extensive evidence that obesity increases cardiovascular risk because cardiovascular risk factors tend to cluster in obese persons, 3,8,9 but there is also evidence from epidemiological studies that relatively low body mass predicts higher cardiovascular risk because of associated systemic diseases.…”
mentioning
confidence: 99%